Dual representation of item positions in verbal short-term memory: Evidence for two access modes - Lange, Elke B. (Eur J Cogn Psychol, 2010)
Memory sets of N = 1~5 digits were exposed sequentially from left-to-right across the screen, followed by N recognition probes. Probes had to be compared to memory list items on identity only (Sternberg task) or conditional on list position. Positions were probed randomly or in left-to-right order. Search functions related probe response times to set size. Random probing led to ramped, “Sternbergian” functions whose intercepts were elevated by the location requirement. Sequential probing led to flat search functions—fast responses unaffected by set size. These results suggested that items in STM could be accessed either by a slow search-on-identity followed by recovery of an associated location tag, or in a single step by following item-to-item links in study order. It is argued that this dual coding of location information occurs spontaneously at study, and that either code can be utilised at retrieval depending on test demands.